Strategies to optimize allow the execution of the budget allocated to the ministry of defence (2013)
The budget execution of the unit of General management of the Ministry of national defense has been affected by the deficiency in the processes implemented to determine projections of execution by each computer spending, given that in the majority of cases these projections do not coincide with the actual execution, is intended to suggest plans of action that transcend any institution that is planned and run more efficiently and effectively the allocated budget the General management of the Ministry of finance and public credit unit.